2022
DOI: 10.1001/jamaneurol.2022.2141
|View full text |Cite
|
Sign up to set email alerts
|

Adult-Onset Genetic Central Nervous System Disorders Masquerading as Acquired Neuroinflammatory Disorders

Abstract: ImportanceAdult-onset genetic disorders may present with clinical and magnetic resonance imaging (MRI) features suggestive of acquired inflammatory diseases. An ever-growing number of potentially treatable adult-onset genetic neuroinflammatory disorders have been described in the past few years that need to be rapidly identified.ObservationsAdult-onset acquired neuroinflammatory disorders encompass a large group of central nervous system (CNS) diseases with varying presentation, MRI characteristics, and course… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 84 publications
0
8
0
Order By: Relevance
“…Low-titer false-positive antibodies (eg, GAD, voltage-gated potassium channel) were a common contributor to misdiagnosis in this series 19 . See table 7-3 20,21 for clues to mimics of paraneoplastic neurologic syndromes that require rapid diagnosis and treatment.…”
Section: Clinical Evaluation Of Paraneoplastic Disordersmentioning
confidence: 80%
See 1 more Smart Citation
“…Low-titer false-positive antibodies (eg, GAD, voltage-gated potassium channel) were a common contributor to misdiagnosis in this series 19 . See table 7-3 20,21 for clues to mimics of paraneoplastic neurologic syndromes that require rapid diagnosis and treatment.…”
Section: Clinical Evaluation Of Paraneoplastic Disordersmentioning
confidence: 80%
“…Low-titer false-positive antibodies (eg, GAD, voltage-gated potassium channel) were a common contributor to misdiagnosis in this series. 19 See TABLE 7-3 20,21 for clues to mimics of paraneoplastic neurologic syndromes that require rapid diagnosis and treatment. Once a paraneoplastic syndrome is suspected, it is important to obtain a thorough history including prodromal symptoms, risk factors for cancer, and autoimmunity in the patient and their genetic relatives; conduct a thorough physical examination including full skin, testicular, breast, and gynecologic examinations and full-body lymph node examination (especially supraclavicular lymph nodes); and then choose how to send serum and CSF for diagnostic tests.…”
Section: Key Pointmentioning
confidence: 99%
“…This is feasible and can be done after discussing non-disclosure protocols and taking appropriate informed consent. The genetic counselors must consider all such situations and provide information to patients in order to facilitate non-directive decision making (57,58).…”
Section: Genetic Counseling For Adult-onset Genetic Diseasementioning
confidence: 99%
“…Yet, despite symptomatic heterogeneity, emerging structural magnetic resonance imaging (MRI) studies have found specific patterns of alterations in the brain's cortical structure in the majority of cases 10–13 . Therefore, recognizing the conditions related to brain cortical changes might be an effective population‐based approach to recognizing alterations in brain function and early‐diagnosis disorders in the brain 14,15 . However, to date, no available evidence has revealed the association between periodontitis and brain cortical structures.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] Therefore, recognizing the conditions related to brain cortical changes might be an effective population-based approach to recognizing alterations in brain function and early-diagnosis disorders in the brain. 14,15 However, to date, no available evidence has revealed the association between periodontitis and brain cortical structures.…”
mentioning
confidence: 99%